Reactivation mechanisms and related-porosity enhancement of shear zones in the context of basement-hosted uranium mineralization: case of the Spitfire discovery in the Patterson Lake corridor, Canada. Issue 3 (2021) - Abdelrazek, Maher; Benedicto, Antonio; Gerbeaud, Olivier; Ledru, Patrick
No abstract available